METHOD FOR DETERMINING EFFECTIVE DESIGN PARAMETERS OF THE MOLD AND TECHNOLOGICAL MODES OF ITS FILLING USING MOLDEX 3D - SYNYUK, OLEG; POLISHCHUK, ANDRII; KUNTSOV, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Using Moldex3D software allows you to determine the effective structural parameters of the mold and the technological modes of its filling, reducing the likelihood of defects and increasing the efficiency of the production process. Modeling the injection molding process in Moldex3D allows for a detailed analysis of various stages of the technological process: filling, cooling, holding under pressure and ejecting the product from the mold, which significantly reduces the time and resources spent on experimental mode settings. During the research of the injection molding process of polymer materials in the Moldex3D system, it was found that the holding and cooling stages play a key role in ensuring the quality of the finished part. The use of molds with a cooling system will reduce the duration of the sole holding process, which will contribute to increasing production productivity as a whole. At the same time, with a significant decrease in the temperature of the mold walls, premature solidification of the material is observed, which leads to shrinkage. The study of the process of feeding the sole during its holding under pressure showed that at an injection pressure of 155 MPa, the time for feeding additional material into the mold cavity is reduced by 1.5 times, which allows increasing production productivity. However, excessively high injection pressure and temperature of the mold walls can contribute to the formation of flaking, i.e. excess polymer material in the form of a thin lip or protrusion on the edge of the component. It is usually thin and can be easily trimmed, so flaking can be considered a minor defect, but an additional operation to remove it leads to an increase in the cost of the production process. It has been established that the joint lines are zones of reduced performance properties of products due to lower adhesion between the flows, and the placement of joints in the finished product is influenced by the relative location of the mold inlet holes. Therefore, when designing molds, one should choose such a location of the inlet holes that ensures either the location of the joint line in areas that are not subjected to significant loads during the operation of the product, or a change in the orientation of the joints relative to the direction of the applied load. Reducing the angle between the joint line and the direction of the load allows to increase the strength and wear resistance of the products during their operation.